URGENSI PENEGAKAN HUKUM TERHADAP KASUS CYBERSQUATTING DAN PERLINDUNGAN NAMA DOMAIN DI INDONESIA - Gayatri, Gusti Ayu Dyah; Sukmaningsih, Ni Komang Irma Adi; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2025)
This study aims to analyze the legal issues related to the practice of cybersquatting in Indonesia and highlight the urgency of developing specific regulations from the perspective of prevailing positive legal norms. The research adopts a normative legal method with a statutory and conceptual approach, utilizing secondary data obtained through literature study and analyzed using qualitative juridical techniques. The findings reveal that: (1) The regulation of cybersquatting in Indonesia remains general and lacks specific provisions, despite the existence of the Electronic Information and Transactions (ITE) Law; (2) There is a legal vacuum that complicates law enforcement efforts against cybersquatting perpetrators; and (3) Comprehensive regulatory development is needed to strengthen legal protection of trademarks in the digital domain. Therefore, the government should promptly formulate and enact more assertive and detailed legislation on cybersquatting to safeguard trademark owners' rights and prevent further economic losses in the future.